An appraisal of fund of funds efficiency based on risk-adjusted performance measures: Application of an augmented WASPAS methodology - Mostafa Shabani; Ali Khodarahmi; Rouzbeh Ghousi; Emran Mohammadi; Hossein Ghanbari (PLoS ONE, 2025)
In the complex landscape of investment management, Fund of Funds play a crucial role in constructing diversified portfolios with professional oversight. However, evaluating the performance of Fund of Funds is a challenging task due to their intricate management layers and diverse underlying assets. Traditional performance assessment methodologies often fall short in capturing these complexities, leading to potential inefficiencies in decision-making. This study addresses these challenges by applying a Multi-Attribute Decision Making approach, specifically an augmented Weighted Aggregated Sum Product Assessment methodology, to provide a comprehensive appraisal of Fund of Fund performance. This study introduces an innovative modification to the Weighted Aggregated Sum Product Assessment methodology, addressing its inherent limitations and providing a more advanced evaluative framework. Despite its ability to offer a structured basis for decision-making, this approach has certain constraints, particularly in identifying the most influential performance criteria impacting outcomes. To resolve this issue, the proposed modification incorporates entropy measures and effective weighting techniques, thereby enhancing the robustness and precision of performance evaluation. This approach provides a sophisticated evaluative framework, facilitating investors in making informed decisions and optimizing investment strategies. This methodology was tested on a set of Iranian Fund of Funds, with computational results demonstrating the strong performance and robustness of the proposed approach. Among the alternatives evaluated, TMSK emerged as the best-performing fund, highlighting the effectiveness of the modified Weighted Aggregated Sum Product Assessment method in facilitating informed investment decisions and optimizing portfolio strategies.